The influence of full-thickness supraspinatus tears on abduction moments: the importance of the central tendon. (May 2019) - Thompson, Simon M.; Prinold, Joe A. I.; Hill, Adam M.; Reilly, Peter; Emery, Roger J. H.; Bull, Anthony M. J.
Background: Detachment of the central tendon of the supraspinatus from its insertion is considered to be crucial to functional deficit. The aim of the present study was to assess the function of the supraspinatus in terms of abduction moments by introducing different tear configurations to assess the functional effect of the central tendon insertion. Methods: Ten fresh frozen shoulders from five cadavers were prepared for testing. A testing protocol was established to measure the abduction moment of the supraspinatus under physiological loading tailored to the anthropometrics of each specimen. Four conditions were tested: intact supraspinatus; complete detachment of portion of the supraspinatus tendon anterior to the main central tendon; detachment of the main central tendon; and detachment of the region of the supraspinatus posterior to the main central tendon. Results: There was a significant and large reduction in abduction moment when the central tendon was sectioned ( p < 0.05). A smaller reduction in abduction moment was found when the regions anterior and posterior to the main central tendon were sectioned ( p < 0.05). Conclusions: The central tendon is vital in the role of functional arm abduction through force transmission through the intact rotator cuff. Reinsertion of the central tendon in the correct anatomical location is desirable to optimize functional outcome of surgery.